Spinodals and critical point using short-time dynamics for a simple model of liquid - Loscar, Ernesto Selim (2016)
We have applied the short-time dynamics method to the gas-liquid transition to detect the supercooled gas instability (gas spinodal) and the superheated liquid instability (liquid spinodal). Using Monte Carlo simulation, we have obtained the two spinodals for a wide range of pressure in sub-critical and critical conditions and estimated the critical temperature and pressure. Our method is faster than previous approaches and allows studying spinodals without needing equilibration of the system in the metastable region. It is thus free of the extrapolation problems present in other methods, and in principle could be applied to systems such as glass-forming liquids, where equilibration is very difficult even far from the spinodal. We have also done molecular dynamics simulations, where we find the method again able to detect the both spinodals. Our results are compared with different previous results in the literature and show a good agreement.